Bone patch composite stent

By designing a composite scaffold composed of PLA or PCL frame and porous G-BCP bioactive filler in skull defect repair, the problems of high bone collection cost and weak bone integration in traditional technology are solved, and efficient skull repair and New bone formation.

CN222444898UActive Publication Date: 2025-02-11ALLIFE REGENERATIVE MEDICINE TECH BEIJING CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202420926369.4
Authority / Receiving Office
CN · China
Patent Type
Utility models(China)
Current Assignee / Owner
Filing Date
2024-04-30
Publication Date
2025-02-11
Estimated Expiration
2034-04-30

AI Technical Summary

Technical Problem

The prior art has problems such as high bone collection cost, limited bone source and weak bone integration in the repair of skull defects, and traditional bone substitutes such as titanium plates and polyether ether ketones have poor tensile properties and high Young's modulus. .

Method used

A composite stent of bone patch was designed, using PLA or PCL frames combined with porous G-BCP bioactive fillers, and prepared by 3D printing, photocuring and freeze-drying technology. The frame adopts a uniformly arranged double-layer hexagonal mesh. lattice structure and coat the surface with magnesium ions or icariin to promote cell growth and vascularization.

Benefits of technology

Efficient repair and new bone formation of bone defects are achieved, mechanical strength and biocompatibility are improved, and the shape and size of the stent can be adjusted according to actual conditions to meet personalized needs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN222444898U_ABST
    Figure CN222444898U_ABST
Patent Text Reader

Abstract

The utility model discloses a bone patch composite stent. A G-BCP (at) PLA bone patch composite stent is prepared through a combined method of 3D printing and freeze drying. The composite scaffold is composed of a 3D printed PLA (or PCL) double-layer hexagonal support frame and a porous G-BCP bioactive filler, and is loaded with an active factor BMP, magnesium ions or icariin. The composite scaffold has the mechanical strength (20-40 MPa) and flexibility equivalent to those of cancellous bones, highly interconnected pores (the porosity is 40-70%), good osteoconductivity, osteoinductivity and vascularization promotion and appropriate degradation rate. The bone patch stent is free of cytotoxicity and can be converted into a clinical product so as to meet personalized, accurate and efficient bone reconstruction requirements of patients with large-area bone defects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The utility model belongs to the field of bone repair and relates to a bone patch composite bracket. Background Art

[0002] Reconstruction of large craniofacial bone defects caused by congenital malformations, trauma, cancer, etc. remains a common clinical challenge. Traditional treatments usually involve transplanting bone tissue from the patient's own or allogeneic bones to the defect area to restore the function and aesthetic appearance of the skull. However, these methods have a series of problems, such as high bone harvesting costs, limited bone sources, and donor site complications. In addition, clinically used bone substitutes such as titanium plates and polyetheretherketone (PEEK) have disadvantages such as poor stretchability, excessively high Young's modulus, weak bone integration, and significant tissue friction (Lu et al, Nature Communications. 2022.13:2499). Therefore, designing and constructing safe and efficient scaffolds for the repair of skull defects has become a hot topic in bone regenerative medicine.

[0003] Bone tissue engineering (BTE) provides another solution for skull regeneration. BTE utilizes the synergistic effect of cells, bioactive molecules and biomaterial scaffolds to induce bone regeneration at the bone defect site by constructing bone grafts. At present, biomaterials used for bone transplant scaffolds are mainly divided into two categories: inorganic materials and polymers. Inorganic materials, such as bioceramics (such as hydroxyapatite HA, tricalcium phosphate β-TCP, and their combination is called "biphasic calcium phosphate" BCP), are known for their excellent biocompatibility, osteoconductivity and bioresorbability. However, HA and β-TCP used alone have the problems of high brittleness and poor mechanical properties, and usually need to be compounded with other materials such as hydrogels (such as collagen, alginate, gelatin, etc.) to form a bionic porous scaffold. Utility Model Content

[0004] In order to solve the technical problems existing in the prior art, the utility model provides the following technical solutions:

[0005] The utility model provides a bone patch composite bracket, which includes a first bracket, a second bracket, a connecting piece, and a filling layer. The first bracket and the second bracket are fixedly connected by the connecting piece, and the hollow part between the first bracket and the second bracket is filled with the filling layer; the first bracket and the second bracket are both composed of a hexagonal frame, and the sides of the hexagonal frames of the first bracket and the second bracket are aligned.

[0006] Furthermore, the material of the filling layer is composed of G-BCP bioactive filler.

[0007] In some embodiments, the bone patch is used for bone repair, and bone repair includes repair of the skull, trunk bones, and limb bones. The skull includes the frontal bone, ethmoid bone, sphenoid bone, occipital bone, parietal bone, temporal bone, nasal bone, lacrimal bone, palatine bone, maxilla, inferior turbinate, zygomatic bone, mandible, hyoid bone, and vomer; the trunk bones include the clavicle, scapula, sternum, ribs, spine, cervical vertebrae, thoracic vertebrae, lumbar vertebrae, sacrum, and hip bone; the limb bones include the humerus, ulna, radius, scaphoid bone, lunate bone, triquetrum, pisiform bone, trapezium, trapezium, capitate bone, hamate bone, metacarpal bone, finger bone, femur, patella, tibia, fibula, calcaneus, talus, navicular bone, cuboid bone, cuneiform bone, metatarsal bones, and toe bones.

[0008] Furthermore, the porosity of the G-BCP bioactive filler after filling is 40%-70%.

[0009] In some embodiments, the porosity of the G-BCP bioactive filler after filling is 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%.

[0010] Furthermore, the mechanical strength of the G-BCP bioactive filler after filling is 20 to 40 MPa.

[0011] In some embodiments, the mechanical strength of the G-BCP bioactive filler after filling is 20 MPa, 21 MPa, 22 MPa, 23 MPa, 24 MPa, 25 MPa, 26 MPa, 27 MPa, 28 MPa, 29 MPa, 30 MPa, 31 MPa, 32 MPa, 33 MPa, 34 MPa, 35 MPa, 36 MPa, 37 MPa, 38 MPa, 39 MPa, and 40 MPa.

[0012] Furthermore, the G-BCP bioactive filler includes GelMA, nano-HA, β-TCP and water.

[0013] The term "GelMA" used in this article refers to methacrylated gelatin, which is obtained by the reaction of gelatin (Gelatin) and methacrylic anhydride (MA). It is a photosensitive biomaterial with biocompatibility, degradability, hardness and the ability to promote cell attachment and growth.

[0014] The term "HA" used in this article refers to nano-hydroxyapatite, which is an artificial synthetic material that simulates the inorganic components of natural bone, has excellent biocompatibility and biosafety, can be tightly integrated with bones and is easy to shape.

[0015] The term "β-TCP" used in this article is also called "TCP", which refers to β-tricalcium phosphate, which has good biodegradability, biocompatibility, and biotoxicity. When it is implanted in the human body, the phosphate and calcium carbonate generated after degradation can enter the biological circulatory system to promote the formation of new bone tissue (or the regeneration and repair of bone tissue). β-tricalcium phosphate belongs to the trigonal crystal system with a calcium-phosphorus ratio of 1.5. It is a stable phase of calcium phosphate at room temperature.

[0016] Furthermore, the substitution degree of the GelMA is 75%-90%.

[0017] In some embodiments, the degree of substitution of the GelMA includes 75%, 76%, 77%, 78%, 79%, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%.

[0018] Furthermore, the substitution degree of the GelMA is 75% or 90%.

[0019] The term "degree of substitution" as used herein is understood to mean the grafting rate of methacrylic anhydride onto gelatin. The degree of substitution can adopt values ​​between 75% and 90%.

[0020] Furthermore, the mass concentration of the GelMA is 10%-15%.

[0021] In some specific embodiments, the mass concentration of GelMA is 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, or 15%.

[0022] Furthermore, the mass concentration of the HA is 5%-15%.

[0023] In some specific embodiments, the mass concentration of HA is 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, and 15%.

[0024] Furthermore, the mass concentration of the β-TCP is 5%-15%.

[0025] In some specific embodiments, the mass concentration of β-TCP is 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, or 15%.

[0026] In some embodiments, the mass concentrations of GelMA, HA, and β-TCP are 10%-15%, 5%-15%, and 5%-15%, respectively, and the mass concentrations of the three are freely combined within their respective ranges.

[0027] Furthermore, the G-BCP bioactive filler also includes the osteogenic factor BMP2.

[0028] Furthermore, the final concentration of the osteogenic factor BMP2 is 20 μg / mL.

[0029] The term "BMP2" as used herein refers to bone morphogenetic protein 2, a secreted ligand of the TGF-β (transforming growth factor-β) protein superfamily. Ligands of this family bind to various TGF-β receptors, leading to the recruitment and activation of SMAD family transcription factors that regulate gene expression.

[0030] In some embodiments, the G-BCP bioactive filler is prepared by the following steps: HA and β-TCP are dissolved in DPBS, shaken, and crushed, and then the mixed solution is placed in a 37°C water bath to continue to dissolve; GelMA is added to the mixed solution under light-proof conditions, and after shaking, it is placed in a 37°C water bath in the dark to dissolve, and shaken every 30 minutes; after sufficient dissolution (with or without adding BMP2 and LAP), it is shaken and placed in a 37°C water bath for insulation to obtain the G-BCP bioactive filler.

[0031] As used herein, "LAP" refers to lithium phenyl-2,4,6-trimethylbenzoylphosphite, which is a water-soluble, cell-compatible type I photoinitiator that can be used for the polymerization of hydrogels or other polymer materials.

[0032] In some embodiments, the GelMA is prepared by the following steps: pour gelatin into DPBS, stir to dissolve, add chloroform, invert at 4°C overnight, remove residual chloroform, dissolve in a 37°C water bath, stir at 50°C after complete dissolution, slowly add MA, and react in the dark; centrifuge the solution, adjust the pH value to neutral, transfer to a dialysis bag, add chloroform and seal, place in 40°C pure water and stir for 72 hours, and change the pure water every 2-4 hours; after the dialysis is completed, the solution is frozen at -20°C or -80°C overnight, and then freeze-dried for 3-4 days to obtain a dry GelMA freeze-dried product. In some embodiments, the final concentration of gelatin used is 10% w / v. The MA drop flow rate is maintained at 1s / drop. In some embodiments, the ratio of MA to gelatin is determined based on the grafting rate of the GelMA that is ultimately desired. In some embodiments, the grafting rate of GelMA herein is 75%-90%, and thus the ratio of MA to gelatin is any ratio between 1.25 mL: 1 g and 1.5 mL: 1 g.

[0033] Furthermore, the first bracket, the second bracket and the connecting piece are made of one of PLA, PLGA and PCL.

[0034] Furthermore, the first bracket, the second bracket and the connecting piece are made of PLA.

[0035] Furthermore, the first bracket, the second bracket and the connecting piece each have a coating, and the coating is composed of magnesium ions or icariin.

[0036] Furthermore, the coating includes a pharmaceutically acceptable small molecule.

[0037] Further, the pharmaceutical small molecule includes a cytotoxic agent, an anticancer agent, an antineoplastic agent, a chemotherapeutic agent, an antitumor agent, an antiviral agent, an antibacterial agent, an anti-inflammatory agent, an immunomodulator, an immune response checkpoint agent, a biological response modifier, a cytokine, a chemokine, a vitamin, a steroid, a ligand, an analgesic, a radiopharmaceutical, a radioisotope, or a dye for visual detection.

[0038] The term "icariin (ICA)" used in this article is an extract of the dried stems and leaves of Epimedium, which is the main active ingredient of Epimedium and a type of traditional Chinese medicine monomer with important application value.

[0039] Furthermore, holes are provided on the edge of the composite bracket.

[0040] Furthermore, the composite support also includes a titanium nail, which can pass through the hole at the edge of the composite support and can be nailed into the defective bone end.

[0041] Furthermore, the composite scaffold is adjusted in shape and size according to the characteristics of the bone defect.

[0042] In some embodiments, the shape of the composite scaffold is not fixed, and its size or shape is determined according to the actual bone defect of the patient with bone defect, and can be any shape such as round, square, oval, etc. In some embodiments, the position of the titanium nail is located at the part where the edge of the composite scaffold overlaps with the bone defect. Generally speaking, the position of the titanium nail is located at the edge of the composite scaffold. In some embodiments, the number of the titanium nails is determined according to the degree of bone defect of the patient with bone defect in actual conditions, with the purpose of being able to fix the composite scaffold to the bone defect. In some embodiments, the size and shape of the holes provided on the edge of the composite scaffold and the titanium nails used for fixing are matched for use.

[0043] In some embodiments, the composite scaffold is prepared by the following steps: 3D modeling of the bone defect portion, 3D printing of the framework using one of PLA, PLGA, and PCL, coating with magnesium ions or icariin coating, adding G-BCP bioactive filler to the framework, freezing at -20°C for the first time, curing with 405nm ultraviolet light, freezing at -20°C for the second time overnight, and freeze-drying to prepare the composite scaffold. The first freezing time at -20°C includes 24 hours.

[0044] In some embodiments, the frame volume of the PLA, PLGA, PCL material accounts for 25%-30%, and the G-BCP bioactive filler accounts for 70%-75%. In some embodiments, the G-BCP bioactive filler is kept in a light-proof condition before the light curing operation.

[0045] Furthermore, the first bracket and the second bracket in the composite bracket are evenly arranged, and the connecting member includes a connecting rod with a height consistent with the thickness of the bone.

[0046] Furthermore, the skeleton includes a skull, trunk bones, and limb bones.

[0047] Furthermore, the skull includes frontal bone, ethmoid bone, sphenoid bone, occipital bone, parietal bone, temporal bone, nasal bone, lacrimal bone, palatine bone, maxillary bone, inferior turbinate, zygomatic bone, mandible, hyoid bone and vomer.

[0048] Furthermore, the trunk bones include shoulder clavicles, scapulae, sternum, ribs, spine, cervical vertebrae, thoracic vertebrae, lumbar vertebrae, sacrum and coccyx, and hip bones.

[0049] Furthermore, the limb bones include the humerus, ulna, radius, scaphoid, lunate, triquetrum, pisiform, trapezium, trapezium, capitate, hamate, metacarpal bones, phalanges, femur, patella, tibia, fibula, calcaneus, talus, navicular, cuboid, cuneiform, metatarsal bones, and phalanges.

[0050] Furthermore, the height of the connecting piece can be flexibly adjusted according to the thickness of the defective bone.

[0051] Furthermore, the connecting member includes a connecting rod with a height of 10 mm.

[0052] Furthermore, the connecting piece comprises a columnar body with a diameter of 3 mm and a height of 10 mm.

[0053] Furthermore, the side length of a single hexagonal frame of the first bracket and the second bracket is 8 mm.

[0054] Furthermore, the frame composed of the first bracket, the second bracket and the connecting member is in a grid shape as a whole.

[0055] In some embodiments, the overall shape of the framework composed of the first support, the second support, and the connector depends on the 3D reconstructed shape of the bone defect site.

[0056] Furthermore, the frame composed of the first bracket, the second bracket and the connecting member is in the same horizontal plane or in an arc shape as a whole.

[0057] Beneficial effects:

[0058] The utility model obtains a porous G-BCP scaffold by optimizing the mixing ratio of GelMA, nanoscale HA, and β-TCP. FDA-approved polymers for bone repair, such as PLA, PLGA, and PCL, have high mechanical strength and stiffness, and natural polymers have the advantage of biocompatibility. PLA has the characteristics of thermal stability, cell compatibility, and non-toxic degradation products, and usually exists in the form of PLGA, which has very good biocompatibility, biodegradability, and adjustable mechanical properties. PCL has good solubility, low melting point, and excellent mixing compatibility. PLA degrades within 6-24 months, while PCL degrades more slowly (3-4 years) due to its high hydrophobicity, so it is very useful for the development of long-term implantable devices. Therefore, the utility model combines PLA (or PCL) and porous G-BCP to mimic the mechanical load-bearing properties required for bone tissue regeneration.

[0059] In response to the problems of slow angiogenesis of larger implants and the need to improve mechanical stability, we designed a biomimetic PLA (or PLGA, PCL) framework based on a honeycomb structure. The framework uses a double-layer hexagonal grid with uniform arrangement, and each point between the two layers forms a stable support through connecting columns. At the same time, the framework is coated with magnesium ions or modified with icariin (ICA), which can be locally released to stimulate cells on the surface and inside the scaffold to form a vascular network, thereby promoting the delivery of nutrients and growth factors, accelerating bone defect healing and new bone formation, promoting calcium deposition and releasing paracrine signals. Finally, the double-layer hexagonal grid on the surface is combined with G-BCP filler to improve the mechanical strength, similar to the compact bone structure; while the porous G-BCP layer with connecting columns forms cancellous bone, realizing the hierarchical distribution of compact bone-cancellous bone-compact bone structure, which is similar to the physiological structure of the human skull.

[0060] The utility model prepares a G-BCP@PLA skull patch composite scaffold by a combination of 3D printing, photocuring molding and freeze drying. The composite scaffold consists of a 3D printed PLA (or PLGA, PCL) double-layer hexagonal grid frame and a porous G-BCP bioactive filler. The frame adopts a double-layer hexagonal grid with uniform arrangement, and each point between the two layers forms a stable support through a connecting column. The frame is modified by adsorbing magnesium ions or icariin, which is used for local release to stimulate cells on the surface and inside the scaffold to form a vascular network, promote nutrient exchange and growth factor delivery. G-BCP filler adds osteogenic factor BMP2 to promote osteogenic differentiation. The filler has mechanical strength (20-40MPa) and flexibility comparable to cancellous bone, highly interconnected pores (porosity 40-70%), good osteoconductivity, osteoinductivity, angiogenesis and a suitable degradation rate. After the filler is filled into the frame, it is photocured into a mold. The double-layer hexagonal grid on the surface is combined with the G-BCP filler to improve the mechanical strength, similar to the compact bone structure; and the porous G-BCP layer containing connecting columns forms a cancellous bone structure, realizing the hierarchical distribution of compact bone-cancellous bone-compact bone structure, which is similar to the physiological structure of the human skull. In addition, the shape and size of the bracket can be adjusted according to actual conditions. It can be square, round or oval. The edge of the entire bracket is anchored to the defective skull surface by titanium nails to ensure its stability. This design enhances the mechanical properties, osteogenic differentiation and vascularization potential of the overall skull patch to meet the patient's personalized, precise and efficient skull reconstruction needs.

[0061] Summarize the advantages of this utility model:

[0062] (1) G-BCP composite materials have extremely high biocompatibility, osteoconduction and osteoinduction, and can recruit autologous bone marrow mesenchymal stem cells (BMSCs) to migrate into the material and distribute evenly, promoting the proliferation and adhesion of BMSCs, differentiation into osteocytes and secretion of a large amount of bone matrix.

[0063] (2) The process is simple and stable, requiring only physical methods such as photocuring cross-linking and low-temperature cold drying. The network structure formed by GelMA in the G-BCP scaffold promotes the transport and exchange of oxygen and nutrients.

[0064] (3) The G-BCP composite material has good mechanical strength of 20-40 MPa (human cancellous bone). Its excellent toughness and resilience enable the scaffold to maintain tension and promote the bone defect repair effect.

[0065] (4) HA itself has antibacterial function, and G-BCP composite materials can also be used for drug delivery and sustained release. G-BCP scaffolds are loaded with osteogenic induction active factor BMP2, and the framework is adsorbed with magnesium ions or modified with icariin ICA. This promotes the migration, proliferation, differentiation, anti-inflammation, and angiogenesis of BMSCs, thereby promoting new bone formation at the bone defect site.

[0066] (5) Appropriate degradation rate. It is estimated that G-BCP will take about 5 to 8 years to be completely degraded in the human body. In addition, the degradation products are calcium ions and phosphorus ions, which circulate in the human blood and are safe, non-toxic and without hidden dangers.

[0067] (6) The viscosity of G-BCP slurry has printable properties, which can realize 3D printing of customized G-BCP stents to meet the personalized needs of clinical patients.

[0068] (7) The stent is non-thermal, non-electrical, and non-magnetic, enabling clinical high-dose, high-resolution MRI or micro-CT examinations.

[0069] (8) The composite bracket of the utility model is combined with the polymer PLA frame by G-BCP filler, and the mechanical stability of the double-layer hexagonal honeycomb PLA frame is better. BRIEF DESCRIPTION OF THE DRAWINGS

[0070] Figure 1 It is a schematic diagram of the overall structure of the utility model;

[0071] Figure 2 It is the 3D modeling of the human skull parietal bone and the PLA / PCL frame design;

[0072] Figure 3 It is the PLA framework design and physical picture, and the physical picture of the G-BCP@PLA scaffold freeze-dried product.

[0073] In the figure, 1, first bracket; 2, second bracket; 3, connecting piece; 4, hexagonal frame. DETAILED DESCRIPTION

[0074] The technical solutions in the embodiments of the utility model are clearly and completely described below through specific embodiments. Obviously, the described embodiments are only part of the embodiments of the utility model, not all of the embodiments. Those skilled in the art can easily understand other advantages and functions of the utility model from the contents disclosed in this specification. The utility model can also be implemented or applied through other different specific implementation methods. In the absence of conflict, the following embodiments and features in the embodiments can be combined with each other. Based on the embodiments in the utility model, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the utility model.

[0075] A bone patch composite bracket, the composite bracket comprising a first bracket 1, a second bracket 2, a connector 3, and a filling layer, the first bracket 1 and the second bracket 2 are fixedly connected by the connector 3, and the hollow part between the first bracket 1 and the second bracket 2 is filled with the filling layer; the first bracket 1 and the second bracket 2 are both composed of a hexagonal frame 4, and the sides of the hexagonal frames 4 of the first bracket 1 and the second bracket 2 are aligned, with reference to Figure 1 .

[0076] In a more specific embodiment, the material of the filling layer is composed of G-BCP bioactive filler.

[0077] In a more specific embodiment, the porosity of the G-BCP bioactive filler after filling is 40%-70%.

[0078] In a more specific embodiment, the mechanical strength of the G-BCP bioactive filler after filling is 20 to 40 MPa.

[0079] In a more specific embodiment, the G-BCP bioactive filler comprises GelMA, HA, TCP and water.

[0080] In a more specific embodiment, the degree of substitution of GelMA comprises 75%-90%.

[0081] In more specific embodiments, the degree of substitution of GelMA is 75% or 90%.

[0082] In a more specific embodiment, the mass concentration of GelMA is 10%-15%.

[0083] In a more specific embodiment, the mass concentration of HA is 5%-15%.

[0084] In a more specific embodiment, the mass concentration of TCP is 5%-15%.

[0085] In a more specific embodiment, the G-BCP bioactive filler further comprises the osteogenic factor BMP2.

[0086] In a more specific embodiment, the first bracket 1, the second bracket 2, and the connecting member 3 are made of one of PLA, PLGA, and PCL.

[0087] In a more specific embodiment, the first bracket 1, the second bracket 2, and the connecting member 3 are made of PLA.

[0088] In a more specific embodiment, the first stent 1, the second stent 2, and the connector 3 each have a coating, and the coating is composed of medicinal small molecules.

[0089] In more specific embodiments, the pharmaceutical small molecule comprises a cytotoxic agent, an anticancer agent, an antineoplastic agent, a chemotherapeutic agent, an antitumor agent, an antiviral agent, an antibacterial agent, an anti-inflammatory agent, an immunomodulator, an immune response checkpoint agent, a biological response modifier, a cytokine, a chemokine, a vitamin, a steroid, a ligand, an analgesic, a radiopharmaceutical, a radioisotope, or a dye for visual detection.

[0090] In a more specific embodiment, said coating consists of magnesium ions or icariin.

[0091] In a more specific embodiment, the composite stent has holes at its edge.

[0092] In a more specific embodiment, the composite stent further comprises titanium nails, and the titanium nails pass through holes at the edge of the composite stent.

[0093] In a more specific embodiment, the connecting member 3 includes a connecting rod whose height can be flexibly adjusted according to the thickness of the bone.

[0094] In a more specific embodiment, the height of the connecting member 3 is variable, the purpose of which is to enable the bone repair material to achieve the supporting strength for bone repair.

[0095] In a more specific embodiment, the connecting member 3 comprises a connecting rod with a height of 10 mm.

[0096] In a more specific embodiment, the connecting member 3 comprises a columnar body with a diameter of 3 mm and a height of 10 mm.

[0097] In a more specific embodiment, the side length of the single hexagonal frame 4 of the first bracket 1 and the second bracket 2 is 8 mm.

[0098] In a more specific implementation scheme, the frame composed of the first bracket 1, the second bracket 2, and the connecting member 3 is in a grid shape as a whole.

[0099] In a more specific embodiment, the overall shape of the frame composed of the first support 1, the second support 2, and the connector 3 depends on the 3D reconstructed shape of the bone defect.

[0100] In a more specific embodiment, the frame composed of the first bracket 1, the second bracket 2, and the connecting member 3 is in the same horizontal plane or in an arc shape as a whole.

[0101] Example 1 Structural design and preparation of G-BCP scaffold

[0102] 1. Experimental materials and equipment

[0103] Gelatin (Sigma-Aldrich, 48722-500G-F); chloroform (CHCl3, domestic); methacrylic anhydride (MA, Sigma-Aldrich, 276685); lithium phenyl-2,4,6-trimethylbenzoyl hypophosphite (LAP, Sigma-Aldrich, 900889); cellulose dialysis bag (D9402-100FT); sodium hydroxide (NaOH, domestic); 90% GelMA (EFL-GM-90, Y00723); nanohydroxyapatite (HA, Aladdin, 1306-06-5); β-tricalcium phosphate (TCP, Aladdin, 7758-87-4); LIVE / DEAD cell viability / cytotoxicity kit (Thermo Fisher Scientific, L3224); Hoechst 33342 live cell staining solution (Biyuntian, C1028); Clostridial peptidase collagenase type I (Yishen Biotechnology, 40507ES60); DMEM phosphate buffered saline (DPBS, Sitofan, SH30028.02); DPBS (containing calcium and magnesium, Thermo Fisher Scientific). Icariin (ICA, Sigma-Aldrich, 489-32-7); 3D modeling and PLA, PLGA, PCL printing (provided by 3D printing custom merchants: Yuechuang Tengyi Design Service Co., Ltd.).

[0104] Instruments and equipment: electronic universal testing machine (DF13.104D), freeze dryer (XZ_JX1.4, Ningbo Xinzhi Freeze Drying Equipment Co., Ltd.), electronic balance (MTW120g / 0.0001g), ultrasonic crusher (Wuxi Hanwu Technology Co., Ltd.), heating digital display magnetic stirrer (IKA), centrifuge (TDZ5-WS). UV curing lamp (EFL-LS-1601-405).

[0105] 2. Experimental methods

[0106] 2.1 Mix methacrylic anhydride and gelatin solution to prepare GelMA. The degree of substitution of GelMA is between 75% and 90%. The following is an example of the preparation steps of GelMA with a degree of substitution of 75%:

[0107] (1) Weigh 20 g of gelatin and pour it into a sterile glass reagent bottle containing 200 mL of DPBS to a final concentration of 10% (w / v). Stir at 50°C and 600 r / min for 3 h to completely dissolve the gelatin.

[0108] (2) Add 10 mL of chloroform to the above gelatin solution and place the bottle upside down at 4°C overnight. The next day, remove the remaining chloroform. Dissolve the gelatin solution in a 37°C water bath and transfer to 50°C and stir at 800-900 rpm after it is completely dissolved.

[0109] (3) Place 25 mL of methacrylic anhydride (MA) in a 125 mL glass separatory funnel and slowly add it dropwise (flow rate controlled at 1 s / drop) into 200 mL of gelatin solution (1.25 mL MA / 1 g gelatin). The addition is completed after about 30 min. Continue stirring at 50 °C and 800 rpm and react for 4 h in the dark.

[0110] (4) The GelMA solution after the reaction in (3) was divided into 50 mL centrifuge tubes and centrifuged at 4000 rpm for 5 min. The supernatant was collected in a glass beaker and the pH was adjusted to 7.0. The neutral solution was transferred to a dialysis bag, and 10 mL of chloroform was added and the bag was sealed. The dialysis bag was placed in pure water at 40°C and dialyzed for 72 h to remove small molecular impurities. The water was changed every 2-4 h.

[0111] (5) After dialysis is completed, the GelMA solution is dispensed into centrifuge tubes and frozen in a -20°C or -80°C refrigerator overnight, then transferred to a freeze dryer and freeze-dried for 3-4 days. The dried GelMA freeze-dried product can be stored at -20°C / -80°C away from light.

[0112] 2.2G-BCP slurry preparation and viscosity test:

[0113] The proportion of G-BCP bioactive filler includes GelMA (10-15%), HA (5-15%), and β-TCP (5-15%), wherein the substitution rate of GelMA can be 75-90%. The following takes 10% GelMA + 7.5% HA + 8% β-TCP (% = w / v) as an example to illustrate the specific steps:

[0114] (1) Weigh 0.6 g HA and 0.64 g β-TCP and dissolve them in 8 mL DPBS. Vortex and shake for 1 min, then use an ultrasonic disruptor to disrupt for 2 min (power 60%; on for 7 s, off for 3 s). Then, place the mixed solution in a 37°C water bath to continue dissolving.

[0115] (2) Weigh 0.8 g of GelMA and add it to the mixed solution of (1) in the dark. Vortex and shake for 2 min. Place in a 37°C water bath in the dark for 4 h to dissolve. Vortex and shake every 30 min.

[0116] (3) After GelMA is fully dissolved and mixed, 8 mL of BMP2 (20 μg / mL) and 480 mL of 5% LAP are added and vortexed, and the mixture is placed in a 37° C. water bath to keep warm for use.

[0117] 2.3 3D modeling based on micro-computed tomography (micro-CT) data:

[0118] Gas anesthesia was used, and single photon emission computed tomography (SPECT / CT) was scanned at 1.3 times (175 μA, 65 kV, 50 μm spot size), and further 3D reconstruction was performed using Victory X-04.2.0.0 software, and image analysis was performed using Arria 4.1.2 software.

[0119] 2.4 Personalized G-BCP@PLA scaffold preparation:

[0120] (1) The 3D printed PLA (or PCL) framework was immersed in a mixture containing 0.18% GelMA, 0.15% HA, 10 mM magnesium ions or icariin ICA with a final concentration of 4 μM and shaken at a low speed for 3 days to modify the PLA (or PCL) framework.

[0121] (2) Take an appropriate amount of G-BCP composite slurry to fill the PLA frame, perform photocuring printing, freeze at -20°C for 24 hours, and then cure with 405nm ultraviolet light. Then, freeze the composite material again at -20°C overnight, and place it in a freeze dryer to dry it. The G-BCP scaffold is prepared. Importantly, in the entire composite scaffold, the volume of the PLA frame accounts for 25-30%, and the volume of the G-BCP filler accounts for 70-75%.

[0122] 3. Experimental results

[0123] G-BCP liquid slurry containing bone induction factor BMP2 was prepared. After 5s of UV cross-linking, the G-BCP slurry quickly solidified to form a hard jelly. In addition, the viscosity (or rheology) of the G-BCP slurry was tested by squeezing with a 1mL syringe. After 2s of UV cross-linking, the G-BCP slurry was squeezed out of the needle to present a continuous milky white line, indicating that the G-BCP slurry has the properties of injectability and printability. The G-BCP slurry was poured into a circular mold with an 8mm diameter and a 2mm diameter and a 4*2*0.8cm silicone groove. After freeze molding, UV cross-linking, and freeze drying, the active G-BCP freeze-dried product was obtained. The compressive strength of G-BCP is 20-40MPa, which is equivalent to the strength of human cancellous bone. Therefore, in order to meet the repair of critical size skull defects, larger G-BCP bone blocks need to further design a support frame to ensure mechanical stability after transplantation.

[0124] Since there is no actual patient defect data, a human skull model was randomly selected, modeled using 3D modeling software Rhino 8.0, and printed using rapid prototyping software 21.0. PLA frame structure design: double-layer hexagonal grids are evenly arranged, each hexagon has a side length of 8mm, and a cylinder diameter (or thickness) of 3mm. The connecting support column between the two layers is a cylinder with a diameter of 3mm and a height of 10mm (the height can be flexibly adjusted according to the thickness of the defective bone). The entire PLA frame is approximately a square 100*100*16mm arc grid ( Figure 2 and Figure 3 ).

[0125] According to the 3D modeling file designed above, use PLA material to print the arc frame ( Figure 3 The framework was soaked for 24 hours to absorb magnesium ions or modified with icariin ICA. The treated PLA framework was integrated with the G-BCP filler by perfusing G-BCP slurry or by layered printing with a light-curing 3D printer. After UV crosslinking and freeze drying, a composite skull patch was obtained ( Figure 3 ).

[0126] The description of the above embodiments is only used to understand the method and core idea of ​​the utility model. It should be pointed out that for ordinary technicians in this field, several improvements and modifications can be made to the utility model without departing from the principle of the utility model, and these improvements and modifications will also fall within the scope of protection of the claims of the utility model.

Claims

1. A bone patch composite scaffold, characterized in that: include: A first bracket (1), a second bracket (2), a connecting piece (3), and a filling layer, wherein the first bracket and the second bracket are fixedly connected via the connecting piece, and a hollow portion between the first bracket and the second bracket is filled with the filling layer; the first bracket and the second bracket are both composed of a hexagonal frame (4), and the sides of the hexagonal frames of the first bracket and the second bracket are aligned; The edge of the composite bracket is provided with a hole; The composite stent further comprises a titanium nail, and the titanium nail passes through a hole at the edge of the composite stent; The height of the connecting piece is adjusted according to the thickness of the defective bone; The connecting piece comprises a columnar body with a diameter of 3 mm and a height of 10 mm; The side length of the single hexagonal frame of the first bracket and the second bracket is 8 mm; The frame composed of the first bracket, the second bracket and the connecting member is in a grid shape as a whole; The frame composed of the first bracket, the second bracket and the connecting piece is located on the same horizontal plane or in an arc shape.

2. The composite stent according to claim 1, characterized in that: The material of the filling layer is composed of G-BCP bioactive filler.

3. The composite stent according to claim 2, characterized in that: The porosity of the G-BCP bioactive filler after filling is 40%-70%.

4. The composite stent according to claim 2, characterized in that: The mechanical strength of the G-BCP bioactive filler after filling is 20 to 40 MPa.

5. The composite stent according to claim 1, characterized in that: The first bracket, the second bracket and the connecting piece are made of one of PLA, PLGA and PCL.

6. The composite stent according to claim 1, characterized in that: The first bracket, the second bracket and the connecting piece are made of PLA.